2003
DOI: 10.1002/app.12238
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, morphological, and thermal properties of rigid polyurethane foams blown by distilled water

Abstract: Rigid polyurethane foams (PUFs) were prepared from polymeric 4,4Ј-diphenylmethane diisocyanate (PMDI), polyether polyol, 1,4-butanediol, silicone surfactant, and distilled water. The properties of the synthesized PUF samples were investigated with differential scanning calorimetry, scanning electron microscopy, and a Universal testing machine. The density of the PUF was decreased from 173.7 to 41.7 kg/m 3 with an increase in distilled water from 0.5 to 3.0 parts per hundred polyol by weight (php), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 13 publications
1
65
1
3
Order By: Relevance
“…In contrast to the density decrease, strength and its anisotropy (strength ratio of parallel to perpendicular direction) smoothly increases with increasing concentration of surfactant with a maximum at 2 pphp (Figure 6). An earlier work showed simultaneous decreases of compression strength with increasing surfactant concentration [7]. It seems that the compression strength is closely related to the closed cell content and cell size when the density variation is insignificant…”
Section: Compression Strengthmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast to the density decrease, strength and its anisotropy (strength ratio of parallel to perpendicular direction) smoothly increases with increasing concentration of surfactant with a maximum at 2 pphp (Figure 6). An earlier work showed simultaneous decreases of compression strength with increasing surfactant concentration [7]. It seems that the compression strength is closely related to the closed cell content and cell size when the density variation is insignificant…”
Section: Compression Strengthmentioning
confidence: 84%
“…Mechanical properties at room temperature were measured using a Universal Testing Machine (Ametek, Lloyd). Compression strength was determined by ASTM D 1621 at a crosshead speed of 3.0 mm/min with the sample dimension of 30×30×30 mm [7]. The force required for 10% deformation based on the original thickness has been taken as the compression strength of the foam.…”
Section: Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After mixing, the reactants were poured into an open mold (250 × 250 × 100 mm) to produce free-rise foams and were cured for 1 week at room temperature. 18,19 In order to investigate the effect of clay on the physical properties and thermal conductivity of PUF, neat PUF was also prepared and compared to PUF/clay composites. The PUF/clay nanocompisites were synthesized with and without ultrasound to study the effect of ultrasonic cavitation on PUF's properties.…”
Section: Methodsmentioning
confidence: 99%
“…Nichol et al [8] reported the effects of equivalent weight and functionality of polyol on the properties of foams. Recently, Jung et al [9,10] compared the properties of rigid polyurethane foams blown by HCFC-141b with those by distilled water. In their work, however, the structure characteristics and dimensional stability of foams were not referred to, and all of data were only limited to the system water level ranging from 0.5 pph to 3.0 pph.…”
mentioning
confidence: 99%